Relative default rates on corporate loans and bonds - Emery, Kenneth M.; Cantor, Richard (Journal of Banking & Finance, 2005)
We use two alternative matched-set methodologies to examine for differences in loan and bond default rates among US non-financial corporate issuers. Under both methodologies, the data indicate that loan default rates are roughly 20% lower than the bond default rates due to issuers that default on their bonds but avoid bankruptcy and avoid defaulting on their loans. For a small number of European issuers, the data suggest a similar reduction in loan default rates relative to bond default rates. However, the European results differ qualitatively from the US results, due likely to differences in US and European bankruptcy regimes, as well as the larger role of bank debt on most European issuers’ balance sheets. These results have important implications for investors, bank supervisors, and rating agencies that assess the relative expected credit losses on loans versus bonds.